IMPLEMENTASI WAJIB PENDIDIKAN DASAR 12 TAHUN DI KOTA TANGERANG - Dodi Subagia (Batara Wisnu : Indonesian Journal of Community Services, 2021)
The policy of the Tangerang City Government in increasing compulsory basic education that must be taken by its people from 9 years to 12 years, especially in increasing the number of senior high school public schools, is felt by private school managers to be a threat to its continued implementation, with an indication of a decrease in the number of people interested in school in schools that are managed by the private sector. The results of the analysis show that the existence of this policy must be responded positively by private school managers to further improve the quality of learning in schools. In fact, the decline in the number of students in private schools is more dominant by the emergence of new schools that offer a much better quality of learning